Circadian and Dopaminergic Regulation of Fatty Acid Oxidation Pathway Genes in Retina and Photoreceptor Cells. - Patrick Vancura; Tanja Wolloscheck; Kenkichi Baba; Gianluca Tosini; P Michael Iuvone; Rainer Spessert (PLoS ONE)
The energy metabolism of the retina might comply with daily changes in energy demand and is impaired in diabetic retinopathy-one of the most common causes of blindness in Europe and the USA. The aim of this study was to investigate putative adaptation of energy metabolism in healthy and diabetic retina. Hence expression analysis of metabolic pathway genes was performed using quantitative polymerase chain reaction, semi-quantitative western blot and immunohistochemistry. Transcriptional profiling of key enzymes of energy metabolism identified transcripts of mitochondrial fatty acid β-oxidation enzymes, i.e. carnitine palmitoyltransferase-1α (Cpt-1α) and medium chain acyl-CoA dehydrogenase (Acadm) to display daily rhythms with peak values during daytime in preparations of the whole retina and microdissected photoreceptors. The cycling of both enzymes persisted in constant darkness, was dampened in mice deficient for dopamine D4 (D4) receptors and was altered in db/db mice-a model of diabetic retinopathy. The data of the present study are consistent with circadian clock-dependent and dopaminergic regulation of fatty acid oxidation in retina and its putative disturbance in diabetic retina.